2018
DOI: 10.1111/liv.13714
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bile acid profiling in hereditary intrahepatic cholestasis: Genetic and clinical correlations

Abstract: Profiling of plasma bile acids has provided insights into cholestasis alleviation and may be useful for the clinical management of cholestatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Among these genes, we found ABCB11, which encodes the bile salt export pump (BSEP), was involved in bile secretion, cholesterol metabolism, bile acid and bile salt metabolism, and recycling of bile acids and salts based on the pathway analysis. BSEP mediates the secretion of bile acids across the canicular membrane of hepatocytes into bile to provide the osmotic pressure for bile flow [50, 51]. Strautnieks et al found that BSEP is typically absent or greatly reduced due to ABCB11 mutations, and 15% of patients with BSEP deficiency developed hepatocellular carcinoma or CCA [52].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, we found ABCB11, which encodes the bile salt export pump (BSEP), was involved in bile secretion, cholesterol metabolism, bile acid and bile salt metabolism, and recycling of bile acids and salts based on the pathway analysis. BSEP mediates the secretion of bile acids across the canicular membrane of hepatocytes into bile to provide the osmotic pressure for bile flow [50, 51]. Strautnieks et al found that BSEP is typically absent or greatly reduced due to ABCB11 mutations, and 15% of patients with BSEP deficiency developed hepatocellular carcinoma or CCA [52].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty patients with primary defect of bile salt export pump (BSEP) and 37 healthy controls in bile acid profiling investigations were described in former studies (Liu et al, ; Qiu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Serum sample was separated from blood by routine centrifugation, ali‐quoted (50 μl), freeze‐dried and stored at −80°C until bile acid analysis was performed by reversed‐phase ultrahigh‐performance liquid chromatography/multiple‐reaction monitoring‐mass spectrometry (UPLC/MRM‐MS) with negative ion detection as described previously (Han et al, ; Liu et al, ; Qiu et al, ). The quantitation of bile acids utilized standard substances of 60 bile acids included all of the major bile acids and some minor species with 14 deuterium‐labeled analogs of bile acids as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…Notes: Case numbers in boldface indicate subjects of previous reports. 7,[9][10][11][12][13][14][15] Variants in boldface are novel.…”
Section: Discussionmentioning
confidence: 99%